Problems of labor productivity management in difficult epidemiological situation - L. V. Trunkina; T. V. Telyatnikova; N. A. Kuzmina (Омский научный вестник: Серия "Общество. История. Современность")
In modern conditions the problem of labor productivity growth is becoming increasingly relevant. Its enhancement is paid to attention both at the federal level and at the level of enterprises. This article discusses the increase in labor productivity in the face of the epidemiological situation. The main blocks of programs of the national project to increase productivity are highlighted. In the context of the epidemiological situation, there are problems of preserving and improving productivity in connection with the transition of enterprise personnel on various forms of non-standard employment: televodder, flexible work schedule, durability, etc. The impact of a complex epidemiological situation on labor productivity is disclosed, the main competencies of an effective leader (performance leader) are presented